Process for Determining the Cancer Burden of the Hopi Tribe. - Brown, Sylvia R.; Joshweseoma, Lori; Flood, Timothy (Public Health Reports)
The writers describe the process involved in a third study for determining the cancer burden of the Hopi Tribe in the northeastern part of Arizona. In this study, official Hopi enrollment data were compared with Arizona Cancer Registry data. The process involved bringing in a new partner and obtaining tribal, state, and university approvals and signed data exchange agreement between the state and the Hopi Tribe. Technical implementation of the data match needed computer programming and epidemiologic expertise and required an understanding of the community and the culture. Close partnership among Hopi residents and university epidemiologists was important.